Involvement of ubiquitination in Alzheimer’s disease - Lin, Nan; Gao, Xi-Yan; Li, Xiao; Chu, Wen-Ming (Frontiers in Neurology, 2024)
The hallmark pathological features of Alzheimer’s disease (AD) consist of senile plaques, which are formed by extracellular β-amyloid (Aβ) deposition, and neurofibrillary tangles, which are formed by the hyperphosphorylation of intra-neuronal tau proteins. With the increase in clinical studies, the in vivo imbalance of iron homeostasis and the dysfunction of synaptic plasticity have been confirmed to be involved in AD pathogenesis. All of these mechanisms are constituted by the abnormal accumulation of misfolded or conformationally altered protein aggregates, which in turn drive AD progression. Proteostatic imbalance has emerged as a key mechanism in the pathogenesis of AD. Ubiquitination modification is a major pathway for maintaining protein homeostasis, and protein degradation is primarily carried out by the ubiquitin-proteasome system (UPS). In this review, we provide an overview of the ubiquitination modification processes and related protein ubiquitination degradation pathways in AD, focusing on the microtubule-associated protein Tau, amyloid precursor protein (APP), divalent metal transporter protein 1 (DMT1), and α-amino-3-hyroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors. We also discuss recent advances in ubiquitination-based targeted therapy for AD, with the aim of contributing new ideas to the development of novel therapeutic interventions for AD.